Interactionism, Post-interactionism, and Causal Complexity: Lessons From the Philosophy of Causation - Ferreira Ruiz, María; Umerez, Jon (Frontiers in Psychology, 2021)
In biology and philosophy of biology, discussing the notion of interaction leads to discussing interactionism, this is, roughly, the view that rejects gene-centrism and gene determinism and emphasizes the fact that traits of organisms are always the result of genes and environments. It has been held, already for some time, that the nature-nurture problem requires an interactionist solution of sorts, the so-called interactionist consensus. This consensus has been deemed insufficient and challenged by several authors triggering an extension of the debate among contestants and defenders. Unfortunately, part of the problem is that the views on causation that would ground claims about interactionism are not always made explicit in this debate, which renders those views quite tricky to assess. Moreover, it seems to be assumed that causal complexity excludes the possibility of characterizing, distinguishing, or comparing among causal contributions. By turning to a detailed survey of the origin of the debate and to some developments in the philosophy of causation, we will contend that this view is unwarranted, and that much of the debate around interactionism is based on the drawing of this (wrong) conclusion. We also examine implications of this analysis for the project of a framework of inter-identities.